Wideband Omnidirectional Slotted-Waveguide Antenna Array Based on Trapezoidal Slots - Hugo Rodrigues Dias Filgueiras; James R. Kelly; Pei Xiao; I. F. da Costa; Arismar Cerqueira Sodré (International Journal of Antennas and Propagation)
This manuscript presents a novel approach for designing wideband omnidirectional slotted-waveguide antenna arrays, which is based on trapezoidal-shaped slots with two different electrical lengths, as well as a twisted distribution of slot groups along the array longitudinal axis. The trapezoidal section is formed by gradually increasing the slot length between the waveguide interior and exterior surfaces. In this way, a smoother impedance transition between waveguide and air is provided in order to enhance the array operating bandwidth. In addition, we propose a twisting technique, responsible to improve the omnidirectional pattern, by means of reducing the gain ripple in the azimuth plane. Experimental results demonstrate 1.09 GHz bandwidth centered at 24 GHz (4.54% fractional bandwidth), gain up to 14.71 dBi over the operating bandwidth, and only 2.7 dB gain variation in the azimuth plane. The proposed antenna array and its enabling techniques present themselves as promising solutions for mm-wave application, including 5G enhanced mobile broadband (eMBB) communications.